2017
DOI: 10.5888/pcd14.170038
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Correlates, and Time Trends of Multiple Chronic Conditions Among Israeli Adults: Estimates From the Israeli National Health Interview Survey, 2014–2015

Abstract: IntroductionChronic diseases constitute a major public health challenge. The prevalence of multiple chronic conditions (MCC) has increased. The objective of our study was to describe the prevalence, correlates, and time trends of MCC in the Israeli population and among the nation’s 2 main population groups (Jewish and Arab).MethodsTo describe the prevalence of correlates of MCC, we used data from the 2014–2015 Israeli National Health Interview Survey-III (INHIS-III). MCC was defined as having 2 or more of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
4
14
1
Order By: Relevance
“…According to the 2007‐2010 Israeli National Health Interview Survey, the prevalence of overweight in the adult general population of Israel was 35.4%, while obesity was evident in 15.4% of the population . A more recent report indicated that the prevalence of obesity in the general population was 21% . In our cohort of hospitalized patients, the prevalence of overweight was similar to the general population, among patients with and without DM (34% and 36%, respectively).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…According to the 2007‐2010 Israeli National Health Interview Survey, the prevalence of overweight in the adult general population of Israel was 35.4%, while obesity was evident in 15.4% of the population . A more recent report indicated that the prevalence of obesity in the general population was 21% . In our cohort of hospitalized patients, the prevalence of overweight was similar to the general population, among patients with and without DM (34% and 36%, respectively).…”
Section: Discussionsupporting
confidence: 79%
“…In accordance with the results of a systemic review and metaanalysis by Chang et al, 11 25 A more recent report indicated that the prevalence of obesity in the general population was 21%. 26 In our cohort of hospitalized patients, the prevalence of overweight was similar to the general population, among patients with and without DM (34% and 36%, respectively). As for the prevalence of obesity, while it was similar to the aforementioned reports in the group of patients without DM (20%), it was markedly increased in the group of patients with DM (35%), as could be expected in this population.…”
Section: Analysis By Co-morbiditiessupporting
confidence: 68%
“…Sixty two percent of Americans over 65 have more than one chronic condition ( 34 ) and the prevalence of multiple chronic conditions is increasing ( 35 ), due to aging of populations and to increasing diabetes rates. Older adults with multiple chronic conditions account for a large percentage of health spending ( 36 ).…”
Section: Somatic Disease and Multiple Chronic Conditionsmentioning
confidence: 99%
“…According to a national health study conducted on Israelis aged 21 years and older during 2013-2015 (INHIS 3), the prevalences of diabetes, hypertension, and dyslipidemia were 8.4, 20.6, and 30.2%, respectively [42]. The data on diabetes and dyslipidemia of the current control group were similar to those values, but the prevalence of hypertension was about twice as high (41%).…”
Section: Discussionmentioning
confidence: 78%